2006
DOI: 10.1057/palgrave.jt.5740176
|View full text |Cite
|
Sign up to set email alerts
|

How switching costs affect subscriber loyalty in the Turkish mobile phone market: An exploratory study

Abstract: a new customer have been found to be up to six times higher than the costs of retaining existing ones'.1 Moreover, it is known that as customer loyalty increases, the sensitivity of the customer to price decreases.2 In this context, the struggle to protect customer base by acquiring loyal customers through developing long-term relationships is important. Especially in telecommunications services, it is frequently noted that once customers have been acquired and connected to a particular operator's network, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 38 publications
3
33
0
2
Order By: Relevance
“…Another example that provided by [53] who identified how punishments can be used to make families adapt healthy food purchase. Accordingly, the results in this study demonstrated that "switching cost" affects operator contract choice with high relative importance of 35.6%, as confirmed by other studies such as [31] as well as [33]. However, there were no significant effects for both mobile signal strength as well as sales and maintenance outlets availability on consumer decisions and this was even ranked low for mobile service provider contract choices.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Another example that provided by [53] who identified how punishments can be used to make families adapt healthy food purchase. Accordingly, the results in this study demonstrated that "switching cost" affects operator contract choice with high relative importance of 35.6%, as confirmed by other studies such as [31] as well as [33]. However, there were no significant effects for both mobile signal strength as well as sales and maintenance outlets availability on consumer decisions and this was even ranked low for mobile service provider contract choices.…”
Section: Discussionsupporting
confidence: 81%
“…According to many scholars such as [6] Owing to the difficulty to retain customers, many authors [31]- [36] have studied the effect of switching cost on consumer purchase behaviour, and have confirmed its strong effect on consumer choice. [37] defines switching costs as "one-time costs facing the buyer when switching from one supplier's product to another's" (p. 10).…”
Section: Company Factors and Consumer Choicementioning
confidence: 99%
“…Previous studies usually considered the consumer satisfaction as a direct antecedent of consumer loyalty (Turel et al, 2006), or studied the consumer trust next to the satisfaction without considering any casual relationship between satisfaction and trust. The connection between the switching costs and consumer loyalty also have been researched previously (Aydin et al, 2005), but the present study examine the effects of switching costs in a more complex framework together with the satisfaction and trust. Switching costs can be elaborated a more rational reason to behave loyal.…”
Section: Introductionmentioning
confidence: 92%
“…There is a signifi cant relationship between customer loyalty, customer satisfaction, trust and switching costs in the mobile phone market. 4 In this fi ercely competitive arena, subscribers demand tailored products and better services at lower prices, while service providers focus on customer acquisition as their prime business goal. Customer retention has become the key business issue for telecom companies towards the end of the 1990s.…”
Section: Literature Reviewmentioning
confidence: 99%